ALFARABI’S REESTABLISHMENT OF PHILOSOPHY IN THE PHILOSOPHY OF ARISTOTLE - Welnak, Shawn (Science et Esprit, 2020)
It has generally been assumed that Alfarabi’s understanding of Aristotle was distorted by his reliance on Aristotle’s transmitters. Owing to this, scholars regularly resort to seeking Alfarabi’s sources rather than seriously asking whether he could have, nonetheless, accurately grasped Aristotle’s teaching. This essay attempts, primarily through an analysis of the Philosophy of Aristotle, to reassess such assumptions. In particular, it argues that the Philosophy of Aristotle reveals a deep understanding of two aspects of Aristotle’s teaching about philosophy: the way to philosophy and the way to reestablish it when it has become confused or extinct. Rather than merely dogmatically describing Aristotle’s account of the origin, progress and perplexities of philosophy, as many scholars erroneously expect, Alfarabi enacts this account. Starting from the generally accepted opinions of his own time, Alfarabi dramatically portrays man’s experience as man and thus compels his readers to begin philosophizing for themselves. In this way, Alfarabi truly follows Aristotle’s deepest intention.